TAI Type Cooperative Learning Imroves Learning Achivement of Grade 6 Students At SD Negeri 2 Tawangsari - Mayasari, Asri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study learns to learn the  effectiveness  of the Cooperative Type TAI (Team Assisted   Individualization)   learning   model.   From   the   results   of   the   study conducted learning about conductors  and insulators using the Cooperative Type TAI (Team Assisted Individualization) learning model. Specifically learning using the  Cooperative  Learning  Model  Type  TAI  (Team  Assisted  Individualization) further  improves  learning  outcomes,  the  use  of  the Cooperative  Type  TAI learning  model  (Team  Assisted  Individualization)  makes  learning  activities more enjoyable, students are actively involved and students who are learning to learn. In cycle I there were 4 people (36.36%) who were actively involved in learning and in cycle II it increased to 8 people (72.72%). Then student achievement also increased, this can be seen from the evaluation results, namely in cycle 1 the average score was 68.18 and in cycle II the average score was 84.54. This shows that student learning activities in science learning have increased. So it can be concluded that the TAI (Team Assisted Individualization) Cooperative learning model is effective for increasing student activity and achievement.